Success Factors in Greenhouses of Guanajuato, Mxico (Global Journal of Management and Business Research, 2015)
The purpose of this research was to analyze the success factors of greenhouses in the Guanajuato State, Mexico. Data was collected through survey research with a questionnaire completed by owner/managers of greenhouses. Greenhouses are successful because they have survived four years or more. The results indicate that success was based on five of the seven tested variables. Success factors included owner/manager commitment, effective human resources management, use of technology, having financial resources, and effective channel of distribution. This paper discusses the theoretical framework, results and conclusions.
Keywords: greenhouse; mexico; success factors